A method to assess the outcomes of forest product trade on livelihoods and the environment - Kusters, K.; Belcher, B.; Ruíz Pérez, M.; Achdiawan, R. (Center for International Forestry Research, 2005)
As part of a multi-collaborator research project on the potential of non-timber forest product (NTFP) trade for conservation and development the authors designed tools to assess the effects of NTFP trade on people’s livelihoods and the environment. To assess livelihood outcomes of NTFP trade they used the Sustainable Rural Livelihoods framework and identified indicators to capture changes in financial, physical, natural, human and social assets at the household and community level. They also selected indicators to assess livelihood related changes at the national level. To assess the environmental impacts of commercial NTFP production this paper identified indicators at four levels: target species population, land use ecosystem, landscape, and global level. The method presented in this paper is meant to provide a time and cost effective tool to measure the effects of NTFP trade, based on expert judgment. The paper first presents a brief overview of the research project and the challenges faced in the design of the method, followed by a description of the method.